Using electronic resources to support dialogue in undergraduate small-group teaching: the ASTER project - Frances Condron (Association for Learning Technology, 2001)
Of all the learning experiences to which students are exposed in British universities, some of the most intensely demanding and rewarding are those where students and tutor engage in lengthy discussion. For many disciplines, tutorials, seminars and workshops have a special role in developing expertise in applying complex and abstract theories to rich, diverse bodies of material. The ability to present convincing arguments, both written and verbal, is a skill that undergraduates need to acquire.